2019
DOI: 10.1038/s41598-019-48478-6
|View full text |Cite
|
Sign up to set email alerts
|

The Zea mays mutants opaque2 and opaque16 disclose lysine change in waxy maize as revealed by RNA-Seq

Abstract: In maize, opaque2 ( o2 ) and opaque 16 ( o16 ) alleles can increase lysine content, while the waxy ( wx ) gene can enhance the amylopectin content of grains. In our study, o2 and o16 alleles were backcrossed into waxy maize line ( wxwx ). The o2o2o16o16wxwx lines had amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…In maize, the opaque mutant was identified as accumulating 69% more lysine in its endosperm compared to the parental line (Mertz et al, 1964;Wang et al, 2019). Interestingly, lysine accumulation in the endosperm is related to reduced levels of endosperm proteins like alpha-zein in maize (Wang et al, 2019) and hordein in barley (Schmidt et al, 2015). The level of lysine in M4 grains was not higher than that of M5 or GP (data not shown).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In maize, the opaque mutant was identified as accumulating 69% more lysine in its endosperm compared to the parental line (Mertz et al, 1964;Wang et al, 2019). Interestingly, lysine accumulation in the endosperm is related to reduced levels of endosperm proteins like alpha-zein in maize (Wang et al, 2019) and hordein in barley (Schmidt et al, 2015). The level of lysine in M4 grains was not higher than that of M5 or GP (data not shown).…”
Section: Discussionmentioning
confidence: 92%
“…In another study investigating amino acid content in four barley varieties, the authors found diversity in the lysine content of grains (Jood and Singh, 2001). In maize, the opaque mutant was identified as accumulating 69% more lysine in its endosperm compared to the parental line (Mertz et al, 1964;Wang et al, 2019). Interestingly, lysine accumulation in the endosperm is related to reduced levels of endosperm proteins like alpha-zein in maize (Wang et al, 2019) and hordein in barley (Schmidt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Two genes involved in lysine degradation pathway were down‐regulated which also resulted in retaining higher lysine contents. Genes involved in starch metabolism ( sh2 , bt2 and ae1 ) were up‐regulated which led to wrinkled kernel and farinaceous endosperm (Wang et al., 2019). Information of DEGs promotes the introgression of o2 and o16 alleles in waxy maize or other genetic backgrounds.…”
Section: Genetic Basis Of Qpmmentioning
confidence: 99%
“…13b). Using the maize interactome, we also successfully reconstructed regulatory networks involved in starch synthesis pathway [27][28][29][30] and other established pathways (Supplementary Fig. 14; Supplementary Table 7-8).…”
Section: The Interactome Recapitulates the Network Of Important Genesmentioning
confidence: 99%